Legal Certainty of The Independence of The Prosecutor's Office In Indonesia - Ngurah Wahyu Resta (Journal of Social Research, 2025)
The position of the Prosecutor's Office of the Republic of Indonesia has not been explicitly regulated in the 1945 Constitution of the Republic of Indonesia, resulting in inconsistencies related to the independence of the Prosecutor's Office of the Republic of Indonesia, which in existence the Prosecutor's Office of the Republic of Indonesia is positioned to be part of the Judicial Power as well as part of the government (executive) institution. This has an impact on the weak position of the Prosecutor's Office of the Republic of Indonesia in carrying out its function as a prosecution institution in Indonesia. The purpose of this study is to find out the legal certainty of the constitutional regulation of the independence of the Attorney General's Office of the Republic of Indonesia in Indonesia. In the research, the type of research used is a type of research with normative legal research methods. The conclusion in this study is that the independence of the Prosecutor's Office is needed for the benefit of law enforcement by being honest, fair, responsible, and transparent by upholding the principle of fair trial in the principle of equality before the law. Thus, this must be carried out because the prosecutor's institution is a determining factor in the sub-system of legal structure in criminal law enforcement. On the other hand, the constitutional reconstruction of the position of the Attorney General of the Republic of Indonesia should be important, considering that until now the arrangements related to the position of the Attorney General of the Republic of Indonesia have not been implicitly regulated. This has an impact on the independence of the Prosecutor's Office of the Republic of Indonesia which until now is still positioned as part of the judicial power as well as part of the government (executive) institution on the other hand. The constitutional reconstruction of the position of the Attorney General of the Republic of Indonesia can refer to the Constitution of Myanmar and Laos, which in its constitution formulates the regulation of the position, war/function, appointment and removal of the Attorney General in their respective constitutions.